2019
DOI: 10.1108/ijsi-04-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and wettability properties of electrospun polycaprolactone coated with pectin/polyaniline composite for drug delivery application

Abstract: Purpose Over the years, electrical stimulation in drug delivery system holds particular interest in producing spatially and temporally controlled release mechanism. These systems helped in localized doses drugs to be administrated and response efficiently at target site to achieve excellent healing effect in control microenvironment. Extensive research is needed in order to develop versatile electroactive biomaterials in the field of therapeutics applications. This paper aims to discuss this issue. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Sample 90PVDF/10PVA has an optimal tensile strength of 1.72±0.6 MPa and Young's modulus of 22.03±0.5 MPa. Previous study reported that the tensile strength for natural soft collagenous tissues such as cartilage, cornea, nerve, and skin is around 1 to 10 MPa [3,23]. Therefore, based on these findings, the modified electrospun nanofiber meets the requirement as a potential tissue scaffold.…”
Section: Tensile Strength Characterizationmentioning
confidence: 78%
See 1 more Smart Citation
“…Sample 90PVDF/10PVA has an optimal tensile strength of 1.72±0.6 MPa and Young's modulus of 22.03±0.5 MPa. Previous study reported that the tensile strength for natural soft collagenous tissues such as cartilage, cornea, nerve, and skin is around 1 to 10 MPa [3,23]. Therefore, based on these findings, the modified electrospun nanofiber meets the requirement as a potential tissue scaffold.…”
Section: Tensile Strength Characterizationmentioning
confidence: 78%
“…Beads occur due to https://doi.org/10.31436/iiumej.v22i1.1548 incomplete solvent evaporation due to the reduction of dielectric potential resulting from the low viscosity of conductive PVDF polymer solution. In tissue engineering applications, the diameter size of the electrospun will significantly influence the fibrous surface area and volume for cell attachment, where smaller diameter can provide high density for cell cultivation [23][24]. This advantage will greatly benefit the cells or tissues that have limited capacity for endogenous regeneration and/or replacement of defective cells such as those in the brain and nervous system.…”
Section: Morphology Characterizationmentioning
confidence: 99%
“…The samples were dried in an oven at 70 o C for 24 h until constant weight to eliminate water before being placed in a phosphate buffered saline (PBS) for 24 h for degree of swelling studied [14]. The percentage of water adsorption (degree of swelling) was calculated using the formula below:…”
Section: Degree Of Swellingmentioning
confidence: 99%
“…Few studies reported on the combination of polysaccharide materials into PVDF electrospun. Most existing researches have focused on combining of PVDF with other materials such as hydroxyapatite (HA), fibrin, chitosan, collagen, bio-glass, graphene oxide (GO), polycaprolactone (PCL), polyvinyl alcohol (PVA), and gold (Au) [5,7,14]. Therefore, this study utilizes the electrospinning method to fabricate a hybrid single layer polymeric nanofiber using PVDF-Pectin solution and benzalkonium chloride (BAC) as model drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption of moisture/water and the polymeric material's degradation may be advantageous in some applications. Like in pharma sectors, the study of moisture/water absorption is essential in polymer composites used for drug delivery systems for better performance (Mohd Syahir Anwar Hamzah et al, 2019). Water absorption analysis of fillers or matrices is also crucial for civil industries/structures because it should withstand the different climates.…”
Section: Introductionmentioning
confidence: 99%